PETROGENESIS OF KARAMAILI ALKALINE A-TYPE GRANITES FROM EAST JUNGGAR, XINJIANG (NW CHINA) AND THEIR RELATIONSHIP WITH TIN MINERALIZATION - Su Y.; Tang H.; Liu C.; Hou G.; Cong F.; Sylvester P.J.; Qu W. (My University, 2007)
Several types of granites including alkaline granites and alkali feldspar granites are distributed in the Karamaili tectonic belt of East Junggar, Xinjiang, China. Some medium-small tin deposits are located within or near the contact zones of the granitic intrusions. The alkaline granites share all the features commonly observed in peralkaline A-type granites. They contain alkalic mafic minerals such as riebeckite and aegirine; have high contents of SiO2, alkalis, Rb, Th, Zr, Hf, REE (except Eu), and high ratios of FeO*/MgO and Ga/Al; and show strong depletions in Ba, Sr, Eu in the spidergrams. Laser ablation-ICPMS U-Pb zircon geochronology indicates a crystallization age of ca. 305 Ma for the granites; TIMS analyses of the granites found high εNd(T) values of +5.9 to +6.5. Considering their geochemical features, alkaline granites most likely formed by fractional crystallization of granodioritic magmas, which were probably produced by partial melting of lower crustal basaltic to andesitic rocks formed from oceanic crustal materials that were deeply buried during late Paleozoic subduction and accretion. Six molybdenite samples from the Sareshike tin deposit in East Junggar yielded an isochron age of 307 ± 11 Ma (2σ) and a weighted mean model age of 306.5 ± 3.4 Ma, consistent with zircon U-Pb ages of the alkaline granites. Low Re contents (0.323-0.961 ppm) in the molybdenite suggest that they originated from crustal sources related to the alkaline granites. Considering their identical ages, close spatial distribution, and similar sources, we argue that the A-type granites have a genetic relationship with the tin mineralization, and that the same association may be important elsewhere. Copyright © 2007 by The Geochemical Society of Japan.
Keywords: ALKALINE GRANITES; EAST JUNGGAR; PETROGENESIS; RE-OS ISOCHRON; TIN DEPOSITS; ZIRCON U-PB DATING